KORELASI ANTARA KECERDASAN EMOSIONAL, TANGGUNG JAWAB, DAN DISIPLIN PESERTA DIDIK DENGAN HASIL BELAJAR TEMATIK SEKOLAH DASAR - Astri Mirdanda; Muhammad Asrori; Tahmid Sabri (Universitas Tanjungpura, 2020)
AbstractThis study aims to describe the correlation between emotional intelligence, responsibility, and discipline with thematic learning outcomes, its relationship together with thematic learning outcomes; and the percentage of combined contributions to thematic learning outcomes. This research uses descriptive method with quantitative approach implemented in fourth and fifth grade students of Sekolah Dasar Negeri 3 Segedong. The target of this study is all members of the population, it will be more suitable to use the term research subjects. The number of research subjects were 36 students. Data collection using questionnaires. Data analysis techniques used simple correlation and multiple correlation with two and three independent variables. The results of this study indicate that there is a positive and significant correlation between the independent variables with the dependent variable obtained r1y of 0,610, r2y of 0,645, r3y of 0,897, Ry-12 of 0,671, Ry-13 of 0,911, Ry-23 of 0,898, Ry-123 of 0,917 and the combined contribution of the three independent variables is 84%.Keywords: Emotional Intelligence, Responsibility, Discipline, Thematic Learning Outcomes